Serotonin syndrome. Issue 6 (12th May 2022) - Maitland, Stuart; Baker, Mark
Abstract : The serotonin syndrome is a life-threatening adverse drug reaction resulting from excess serotonergic agonism due to interactions between multiple drugs, poisoning, or less commonly due to therapeutic action of a single drug. The central triad of features in serotonin syndrome are altered mental state, autonomic hyperactivity, and neuromuscular abnormalities in the context of a patient with new/altered serotonergic therapy, although not all these features are consistently present in all patients. The severity of serotonin syndrome can be assessed clinically based on the number and severity of features. Severe serotonin syndrome warrants more careful management on a high-dependency unit. In case of temperature exceeding 38.5°C, urgent cooling measures and sedation should be employed, progressing to rapid sequence intubation and paralysis if cooling measures are ineffective.